Program Penyuluhan Pertumbuhan Gigi Anak: Peran Ibu dalam Pencegahan Kasus Persistensi di Puskesmas Mangasa - Zahrawi Astrie Ahkam; Amirah Maritsa; Hasrini Hasrini; Pariati Pariati; Zulkarnain Zulkarnain (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2022)
Dental and oral health education for children is very important to prevent cases of milk tooth persistence. The role of mothers is crucial in ensuring that children receive good dental care. This program aims to increase mothers' knowledge and awareness of children's tooth growth and prevention of persistence cases at the Mangasa Health Center. The methods used include education, interactive discussions, and distribution of educational leaflets. The results of the activities showed a significant increase in mothers' knowledge and awareness of the importance of children's dental care. With this program, it is hoped that cases of milk tooth persistence in children can be minimized.